The frequency of thyroid carcinoma in patients with solitary and multiple nodules utilizing ultrasound guided fine needle aspiration cytology (FNAC): A prospective study (Thyroid carcinoma and U/S guided FNA) - Kadhim, Mohammed A.; Ahmed, Basim S.; Mahdi, Qahtan A. (Journal of the Faculty of Medicine Baghdad, 2010)
Background: Population studies suggest that 3–8% of asymptomatic adults have thyroid nodules. Nodules have a 5–15% prevalence of malignancy. Fine-needle aspiration cytology is the primary and frequently initial tool for assessing the risk of malignancy in thyroid nodules and selecting patients for thyroid surgery.Patients and Methods: This prospective study was done during the period from June 2007 to November 2008. The study includes 141 patients with palpable solitary or multiple thyroid nodules. Only patients with normal or low TSH values were referred for ultrasound examination and ultrasound guided FNAC, which were done using fine needles (G 20).Results: eleven patients (7.8%) have insufficient or non-diagnostic aspirates and were excluded from the study. Of the remaining 130 patients that were included in our study, only 20 patients had thyroid carcinoma (15.3%). Seventy-nine patients (60.7%) had solitary nodule larger than 10 mm in largest dimension and 51 patients (39.3%) had two or more such nodules. The rate of cancer in males with thyroid nodules was higher than in females. The prevalence of thyroid cancer did not differ between patients with a solitary thyroid nodule (12 of 79 patients, 15.1%) and patients with multiple nodules (8 of 51 patients, 15.7%), the deference is statistically insignificant (P = 0.95). A nodule that is one of several nodules had a lower likelihood of being malignant than did a solitary nodule: (8.9% versus 15.1%) (P < 0.001).Conclusion: Ultrasound guided FNAC is the primary and frequently initial tool for assessing the risk of malignancy in thyroid nodules. The prevalence of thyroid cancer did not differ between patients with a solitary thyroid nodule and those with multiple thyroid nodules. FNAC have limited role incytological diagnosis of follicular carcinomas, unless it is confirmed by histopathological diagnosis.